Clinicians' perspectives of immersive tools in clinical mental health settings: a systematic scoping review - Jessica Cushnan; Paul McCafferty; Paul Best (BMC, 2024)
Abstract Background Virtual Reality in mental health treatment has potential to address a wide spectrum of psychological and neurocognitive disorders. Despite the proven benefits, integration into clinical practice faces significant challenges. There is a critical need for research into clinicians' perceptions of virtual reality due to the gap between rapid technological advancements and their adoption in mental health services. Method A scoping review was conducted to comprehensively understand clinicians' perspectives on the application of immersive virtual reality technologies within mental health settings. 4 data bases were searched, from inception, with the search areas of clinicians', technology, perspectives and mental health. The scoping review followed the PRISMA-ScR checklist. All results were thematically analysed to identify and categorise themes with a focus on qualitative analyses of clinicians' experiences and perceptions of VR applications in therapeutic contexts. Results 17 articles were selected, encompassing a range of mental health settings. The findings indicate that the integration of VR in clinical environments is heavily influenced by clinicians' knowledge and experience, with unfamiliarity often leading to scepticism. Positive attitudes towards VR, bolstered by direct experience and training, were found to drive acceptance, as clinicians' acknowledged its potential to complement traditional therapies. However, there are still gaps in understanding VR's therapeutic applications, particularly concerning its impact on human interaction and its suitability for specific patient groups. Balancing VR's clinical benefits with ethical and safety concerns is crucial, especially when working with vulnerable populations. Furthermore, structural and administrative support is essential to overcoming the financial and logistical challenges of VR implementation, ensuring its safe and effective integration into mental health care. Conclusion While VR holds significant potential for enhancing mental health care, its successful integration into clinical practice necessitates addressing existing gaps in knowledge, training, and structural support. By carefully balancing its clinical benefits with ethical, practical, and safety considerations, VR can be effectively utilised as a valuable tool in mental health treatment, providing innovative solutions while ensuring that patient care remains paramount.